From the Editor Emerita. (April 2016) - Doering, Zahava D.
Abstract: Since 1997, Zahava D. Doering has contributed to Curator: The Museum Journal . This is her last issue as Curator editor. The article highlights the key issues for which the journal has provided a platform to its global readership during her editorship. Issues include psychological and physical access, social roles and responsibility, health, museums without walls, crowdsourcing, environmental sustainability, and human rights and diversity. It also extends gratitude to the editorial staff (named), editorial board members, peer reviewers, and authors she has had the honor to have as colleagues in supporting new dialogues for museums and other cultural venues.